Stop-motion animation : frame by frame film-making with puppets and models - Purves, Barry (Bloomsbury, 2014)
"Stop-motion Animation teaches the skills required to develop as a creative stop-motion animator. It explores how all the elements of film-making - camera work, design, colour, lighting, editing, music and storytelling - come together in this unique art form. With advice on how to use the particular types of movement, characters and stories that typify stop-motion, this book is packed with tips and suggestions to help you get the most out of your stop-motion films, accompanied by illustrations and case studies demonstrating how film-making masters through the years have used it in feature films, short films and television. This second edition also introduces and explores two of the biggest innovations of recent years - at opposite ends of the industry. At the top-end, for film-makers with serious budgets, there is 3D printing in the creation of replacement parts for stop-motion characters while at the amateur/student end of the industry there are a variety of cheap, but effective, apps that can turn turn a smartphone into a mini stop-motion studio. The new edition also includes an extended project in each chapter, covering storytelling techniques, selecting an appropriate style, developing a character, set building and lighting, creating a performance and adding music. These projects combine to lead you through the creation of your first one-minute stop-motion animation"--Resumé vydavatele
Chronologický přehled
Obsahuje rejstřík
Keywords: animovaný film; filmová animace; loutkové filmy; animated film; film animation; puppet films; příručky; handbooks and manuals